Nilai Dalam Legenda Oe Honis Pada Masyarakat Desa Babuin Kabupaten TTS - Sanhedri Boimau (Universitas Persatuan Guru 1945 NTT, 2020)
The aim of this research is to describe and explain the values ​​contained in the legend of Oe Honis in the Babuin Village community, TTS Regency. The problem proposed in this research is: “what kinds of values which ​​are contained in the Oe Honis Legend in the community of Babuin Village, Middle Amanuban District, South Central Timor Regency?” The benefits of this research are as follows: (1) to increase knowledge and broaden the horizon about Oe Honis legend; and (2) as one of the references for the government of South Central Timor Regency in compiling and developing the local content material (Muatan Lokal) for the elementary and secondary schools. The theory used in this research is Anthropology of Literature which is a literary work that emphasizes the cultural heritage of the past. The method used in this research is descriptive qualitative research method. The results of this research indicated that the Legend of Oe Honis is formed by two words namely Oe which means 'water' and Honis which means 'life'. So, Oe Honis means the water of life. The term Oe (water) for the people of Babuin Village, TTS Regency is one of the important elements on earth that is needed very much for human life and other types of living creatures. Therefore, for the people of Babuin Village, South Central Timor Regency, Oe Honis is a source of life for human life. Or in other words, where there is Oe (water) there is life. The values ​​contained in the Oe Honis legend, such as: (1) A historical Value as evidence of the legacy that is still preserved to this day like a cattle footprint being digged and found water namely Oe Honis; (2) Religious Value as a Prayer before digging and using the water; (3) Values of life as the attitudes and efforts to utilize the nature; and (4) The values of togetherness as a relationship in the community, such as building the Sonaf (king palace) and mutual cooperation to find water for the need of Babuin community.